Use of Force in Countering Terrorism - Ersen, M. Uğur (IOS Press, 2013)
No nation or culture can achieve peace and security if it ignores the threat of terrorism, either to itself or to others. Terrorists seek to exploit ethnic and religious conflicts, ideological differences and instability, no matter what form it takes, and terrorism undoubtedly presents one of the world’s most serious security challenges. This book presents a collection of lectures delivered at the advanced training course organized by the Centre of Excellence – Defence Against Terrorism (COE-DAT) in September 2008. The aims of this course were to provide a forum for the exchange of views on developments in the terrorist threat and promote wider ranging partnership and cooperation between those engaged in combating terrorism world wide, with a particular emphasis on the use of force in combating terror. The ten papers presented here address subjects including: asymmetrical war, the past and present application of force as a countermeasure, international humanitarian law (IHL) and the balance between liberty and security, organizational communication, cyber terrorism, access to weapons of mass destruction (WMD) and the strategic role of leadership.This wide ranging collection, covering the use of force as well as many other aspects of terrorism, provides an important resource for all those interested in multinational efforts to combat the threat of global terrorism. Inaugurated in 2005, COE-DAT is a NATO accredited Centre of Excellence; a unique centre dedicated to Defence Against Terrorism, which provides DAT training and education at strategic and operational levels and contributes to research efforts.